Total synthesis of (-)-isatisine A - Patel, Pitambar; Ramana, C. V. (Journal of Organic Chemistry, 2012)
A modular total synthesis of (-)-isatisine A is described in which four consecutive metal-mediated transformations have been employed at the final stage. These include [Pd]-catalyzed Sonogashira coupling, [Pd]-catalyzed nitroalkyne cycloisomerization leading to isatogens, and addition of indoles to isatogens using InCl3- and [Rh]-catalyzed oxidative N-heterocyclization of amino alcohol to form the key amide bond. In addition to these, the removal of the protecting groups has also been carried out in a selective fashion employing either catalytic or stoichiometric metal/metal-based reagents.

Total synthesis of the pseudoindoxyl class of natural products - Dhote, Pawan S.; Patel, Pitambar; Vanka, Kumar; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2021)
The pseudoindoxyl sub-structural motif, amongst the large set of the indole class of alkaloids, represents a unique subset of the oxygenated indole class of the alkaloid family. A majority of this class of natural products contains complex bridged/polycyclic scaffolds with interesting biological profiles. They are thus attractive synthetic targets. Starting from 1963, twenty-eight natural products having the pseudoindoxyl scaffold have been isolated, among which the synthesis of 13 natural products has been accomplished. In this review, we highlight the completed as well as the formal total synthesis of the natural products with a spiro-pseudoindoxyl ring, with a focus on their development. The challenges and the future perspective based on the recent developments in the field will also be discussed. We strongly believe that this review will not only update but also attract the attention of researchers in dealing with the synthesis of pseudoindoxyl compounds.